Determinants of outcomes of Public-Private Partnerships (PPP) in infrastructure in Asia - Renato E. Reside; Amado M. Mendoza (University of the Philippines, School of Economics (UPSE), 2010)
This study analyzes cross-country data extracted from a large global database to identify the major risks affecting Asian PPP into six major factors: (1) macroeconomic environment; openness of economy; (2) incentive issues during planning, design and contracting phases; (3) political risk; (4) fiscal capacity of government; (5) firm-embodied traits: level of technical efficiency and capacity of proponents in construction and operations; and (6) other reasons - regulation, credit risk of buyers of output, etc. Policy recommendations are made.
Keywords: 330; Verkehrsinfrastruktur; Infrastruktur; Wirkungsanalyse; Asien